THE ROLE OF NADZIR IN THE MANAGEMENT OF WAQF LAND IN RELIGIOUS AFFAIRS OFFICE (KUA) KADEMANGAN PROBOLINGGO - Sumarno Sumarno; Mohammad Arifin (USRAH: Jurnal Hukum Keluarga Islam, 2022)
This research aims to know the role of nadzir in managing the Waqf land in KUA Kademangan Probolinggo, analyze nadzir Waqf in the management and development of Waqf land in KUA Kademangan City Probolinggo, and analyze how to certify Waqf land in KUA Kademangan Probolinggo. This research is in the nature of field research, which examines the provisions of the applicable law and the facts that apply in social life.This research is empirical juridical research, which is an approach that aims to obtain knowledge about how the legal relationship with society and the factors that affect the implementation of law in society (Mukhalad, 2020). From the results of the study, it was concluded that nadzir in KUA Kademangan Probolinggo in carrying out his duties to manage Waqf land has not been implemented properly. Nadzir of Religious Affairs Office (KUA) of Kademangan District is responsible aboutWaqf, but not as the manager. Nadzir of Religious Affairs Office (KUA) of Kademangan District is only in charge of providing information and administration in recording Waqf land and its vows. KUA of Kademangan district actually has planning and organizing but it does not include Waqf specific management. This is due to the fact that it is not a special office for Waqf management, however it is merged with marriage administration.Keywords: Nadzir, Waqf, KUA Kademangan